Decision Support System for Foundation Beneficiaries Using the Simple Additive Weighting (SAW) Method - Elfrida Tamba (Bahasa Indonesia, 2020)
Receipt of compensation funds for underprivileged students needs to be selected so that they are not wrong in providing assistance, so that the recipients of assistance are students who deserve to receive. The decision support system is an effective way of selecting students who need compensation funds. The criteria are as a stage for selecting students who are entitled to grant aid, with these criteria all students who participate in receiving the compensation funds will be ranked. The results of the ranking are based on calculations, the first order is Farhan Rifai with a value of0.8; second place is Sidratul Muntaha with a value of 0.7666